Current concepts in cleft care: A multicenter analysis. Issue 4 (April 2018) - Thiele, Oliver C.; Kreppel, Matthias; Dunsche, Anton; Eckardt, Andre M.; Ehrenfeld, Michael; Fleiner, Bernd; Gaßling, Volker; Gehrke, Gerd; Gerressen, Marcus; Gosau, Martin; Gröbe, Alexander; Haßfeld, Stefan; et al.
Abstract: The current surgical techniques used in cleft repair are well established, but different centers use different approaches. To determine the best treatment for patients, a multi-center comparative study is required. In this study, we surveyed all craniofacial departments registered with the German Society of Maxillofacial Surgery to determine which cleft repair techniques are currently in use. Our findings revealed much variation in cleft repair between different centers. Although most centers did use a two-stage approach, the operative techniques and timing of lip and palate closure were different in every center. This shows that a retrospective comparative analysis of patient outcome between the participating centers is not possible and illustrates the need for prospective comparative studies to establish the optimal technique for reconstructive cleft surgery.